2020
DOI: 10.3390/plants9060719
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Prediction and Genetic Correlation of Agronomic, Blackleg Disease, and Seed Quality Traits in Canola (Brassica napus L.)

Abstract: Genomic selection accelerates genetic progress in crop breeding through the prediction of future phenotypes of selection candidates based on only their genomic information. Here we report genetic correlations and genomic prediction accuracies in 22 agronomic, disease, and seed quality traits measured across multiple years (2015–2017) in replicated trials under rain-fed and irrigated conditions in Victoria, Australia. Two hundred and two spring canola lines were genotyped for 62,082 Single Nucleotide Polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…Increased phenotypic heritability has been shown to have a greater impact on whole-genome prediction accuracies, more so than training set population size and marker density (Zhang et al, 2017 ). Fikere et al ( 2020 ) reported moderate-to-high genomic prediction accuracies using genomic best linear unbiased prediction (GBLUP) models upon evaluating genetic correlations and genomic prediction accuracies for several agronomic, disease, and seed quality traits in canola. The inclusion of genotype-by-environment interaction in the GBLUP model resulted in further, though slight, improvements in predictions.…”
Section: Genomic Selection In Crop Improvementmentioning
confidence: 99%
“…Increased phenotypic heritability has been shown to have a greater impact on whole-genome prediction accuracies, more so than training set population size and marker density (Zhang et al, 2017 ). Fikere et al ( 2020 ) reported moderate-to-high genomic prediction accuracies using genomic best linear unbiased prediction (GBLUP) models upon evaluating genetic correlations and genomic prediction accuracies for several agronomic, disease, and seed quality traits in canola. The inclusion of genotype-by-environment interaction in the GBLUP model resulted in further, though slight, improvements in predictions.…”
Section: Genomic Selection In Crop Improvementmentioning
confidence: 99%
“…The number of breeding programs that have already implemented genomic-assisted breeding has increased considerably in recent years [ 229 , 230 , 231 ]. The use of this approach has been facilitated by the development of high-throughput genotyping techniques (such as genotyping by sequencing and DNA chip arrays) in various important crop species, including maize [ 232 , 233 , 234 ], tomato [ 235 , 236 ], wheat [ 237 , 238 ], and rice [ 239 , 240 ], among others.…”
Section: Gwas Genomic and Phenomic Predictionmentioning
confidence: 99%
“…However, it requires the construction of a prediction pattern by integrating marker information with a phenotypic database in a model training step [53] and has led to fundamental changes in plant breeding programs [58]. Genetic progression is improved by genomic selection in crop breeding programs via phenotypic predictions to select ideal phenotypes, based only on their genomic information [59].…”
Section: Benefits and Challenges Of Genomic-enabled Prediction In Plant Breedingmentioning
confidence: 99%